DETEKSI MOLEKULER PENYAKIT VIRAL NERVOUS NECROSIS (VNN) PADA IKAN KERAPU DI WILAYAH KABUPATEN BULELENG PROVINSI BALI - Rio Aditya Kurniawan; Budi Sugianti; Ni Desak Nyoman Pradnyani; Artanti Tri Lestari; Anwar; I Nyoman Suardana; Wahyu Nurlita; Imanuddin Razak (Techno-Fish, 2023)
Viral Nervous Necrosis (VNN) disease is one of the diseases included in the list of aquatic animal diseases of the World Organization for Animal Health (WOAH) and is a pathogen that poses a threat to grouper aquaculture throughout the world. VNN infection can occur vertically and horizontally and has a mortality rate of up to 100%. This study aimed to detect VNN using molecular methods (PCR) in grouper cultured in Buleleng, Bali. The method used is molecularly by conventional PCR. The results of this study indicated that groupers with VNN showed rotating, solitary swimming and enlarged eyelets (exophthalmos). The internal organs show enlargement of the spleen and kidneys. The liver looks pale and haemorrhage occurs in other internal organs. The results of the PCR examination showed 5 (five) positive samples of VNN with the appearance of a band at 230 bp so that the prevalence of VNN was 25%. From the results of this study, recommendations that can be taken are monitoring and surveillance of VNN need to be carried out continuously in grouper aquaculture, this is necessary to determine actions to be taken quickly if VNN is detected in an aquaculture unit. Keywords: betanodavirus grouper, molecular, PCR, VNN